2021
DOI: 10.1021/acsomega.1c00779
|View full text |Cite
|
Sign up to set email alerts
|

Pomegranate-like Core–Shell Ni-NSs@MSNSs as a High Activity, Good Stability, Rapid Magnetic Separation, and Multiple Recyclability Nanocatalyst for DCPD Hydrogenation

Abstract: A novel pomegranate-like Ni-NSs@MSNSs nanocatalyst was successfully synthesized via a modified Stöber method, and its application in the hydrogenation of dicyclopentadiene (DCPD) was firstly reported. The Ni-NSs@MSNSs possessed a high specific area (658 m 2 /g) and mesoporous structure (1.7–3.3 nm). The reaction of hydrogenation of DCPD to endo -tetrahydrodicyclopentadiene ( endo -THDCPD) was used to evaluate the catalytic performance of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 83 publications
0
6
0
Order By: Relevance
“…As seen in Figure b,c, all samples showed an initial mass loss in the DTG curve at 30–110 °C due to the loss of physically adsorbed water . The CTAB@mSiO 2 displayed a weight loss of 28.7% at 150–500 °C, corresponding to the CTAB decomposition . As the temperature further increased, a slow decrease in weight (4.3%) at 500–650 °C derived from the decomposition of NC dots in mSiO 2 .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…As seen in Figure b,c, all samples showed an initial mass loss in the DTG curve at 30–110 °C due to the loss of physically adsorbed water . The CTAB@mSiO 2 displayed a weight loss of 28.7% at 150–500 °C, corresponding to the CTAB decomposition . As the temperature further increased, a slow decrease in weight (4.3%) at 500–650 °C derived from the decomposition of NC dots in mSiO 2 .…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies found that CTAB can be used as promising precursors to prepare NC dots via the carbonization process. , The repulsive force between the metal particles is greater than the van der Waals force due to the increased CTAB molecules near the metal particles. In this case, the NPs would gradually change from agglomeration to monodispersion . This further inspires us to directly obtain NC dots by utilizing CTAB carbonization to further enhance metal dispersion via the double confinement during the synthesis of mSiO 2 .…”
Section: Introductionmentioning
confidence: 89%
See 3 more Smart Citations